Gendered cognitions: a socio-cognitive model of how gender affects entrepreneurial preferences - Wieland, Alice M., Markus, Kemmelmeier, Vishal K., Gupta; McKelvey, William (Entrepreneurship & Regional Development, 2019)
This research explores the social-cognitive factors which lead both women and men to pursue ventures consistent with their gendered social identity, therefore, reinforcing the gender gap in entrepreneurship. We measured the self-assessments of individuals presented with experimentally manipulated entrepreneurial opportunities that were either consistent or inconsistent with their self-reported gender. A theoretical model derived from Social Role Theory is presented and tested. It posits that a gender match (mismatch) with the entrepreneurial opportunity results in higher (lower) reported self-efficacy, anticipated social resources, and venture desirability and lower (higher) venture risk perceptions. The experimental data are tested in a sequential mediation SEM model. We find evidence that self-efficacy and anticipated social resources mediate the effect of gender congruency on perceived risk and venture desirability. The results provide insight into the insidious barriers that play a role in reproducing a gender gap in entrepreneurial outcomes by ‘nudging’ women into lower-return ventures in less lucrative industries.
_eprint: https://doi.org/10.1080/08985626.2018.1551787
Keywords: Entrepreneur; gender; gender gap; gender norms; gender role; opportunity evaluation; sex

Evaluating the Knowledge of Conversational Agents - Park, Mina; Aiken, Milam; Vanjani, Mahesh (Southwestern Business Administration Journal, 2019)
Keywords: dept.bis; dept.mgt; peer-reviewed

Gender Characterizations in Entrepreneurship: A Multi‐Level Investigation of Sex‐Role Stereotypes about High‐Growth, Commercial, and Social Entrepreneurs* - Gupta, Vishal K.; Wieland, Alice M.; Turban, Daniel B. (Journal of Small Business Management, 2019)
The purpose of this study is to cast new light on possible gender biases in implicit theories people hold about various forms of entrepreneurial activity. Using social role theory, we delve into sex‐role stereotypes associated with high‐ and low‐growth entrepreneurship and commercial and social entrepreneurship. Predictions were tested with an experimental design using both a between‐subject design to capture group‐level stereotypes and a within‐subject design to capture individual‐level stereotypes. Findings reveal that commercial and high‐growth entrepreneurs are perceived as more similar to men than to women and higher on agency than communality. Conversely, low‐growth entrepreneurs are perceived as more similar to women than men, and higher on communality than agency. Social entrepreneurs are uniquely perceived as similar to both men and women, though they are also considered higher on agency than communality. Interestingly, female, but not male respondents, perceive some overlap between the feminine gender role and high‐growth and commercial entrepreneurship. Notably, those higher on modern sexism perceive less overlap between entrepreneurship and femininity. Taken together, our results suggest that commercial high‐growth entrepreneurship is most strongly male‐typed, which is likely to be problematic for women (and non‐traditional men) wanting to start growth‐oriented ventures. Implications and directions for future research are discussed.
_eprint: https://www.tandfonline.com/doi/pdf/10.1111/jsbm.12495
Keywords: dept.mgt; peer-reviewed

Exploring the Gender Gap in Tech Companies: Why Aren't There More Women? - Chaudhry, Haroon; Wall, Alison E.; Wall, Jerry L. (Competition Forum, 2019)
Diversity issues in organizations have long been the subject of organizational studies and cultural examinations. While organizations have made several advancements to balance the presence of female representation in their employees, there remains a paucity of women in certain fields, most notably the tech industry where, despite similar performance in courses, women are alarmingly underrepresented. This paper examines this lack of diversity and proposes some remedies for specifically addressing the lack of women in the tech industry and can be extended to participation in any STEM careers that makes up a significant portion of the tech industry.
Num Pages: 275-280 Place: Indiana, United States
Keywords: Bullying; Business And Economics; Careers; Employees; Employment; Females; Gender; High tech industries; Litigation; Multiculturalism & pluralism; Research & development–R&D; STEM education; STEM professions; Social networks; Success; Women; dept.mgt; peer-reviewed

Industrial Democracy in The Knowledge Society - Nodoushani, Omid; Robbins, Gregory Gadiel (Competition Forum, 2019)
Keywords: dept.mgt; peer-reviewed

Supply chain integration, advanced manufacturing technology, and strategic leadership: An empirical study - Birasnav, M.; Bienstock, Joshua (Computers & Industrial Engineering, 2019)
Top management support is a crucial investment at any manufacturing firm striving to integrate supply chain partners with the manufacturing processes so as to achieve a competitive advantage. Though the effectiveness of different leadership behaviors exhibited in top-level management has been documented in the leadership literature, the influence of such behaviors on developing linkages with supply chain partners has not been extensively examined. In order to bridge this research gap, this study examines the interlinkages between strategic leadership theory and supply chain integration theory. In addition, it also investigates the interrelationships between these two theories in the context of implementation of advanced manufacturing technology. Data has been collected from 107 small manufacturing companies and was analyzed using structural equation modelling. Results show that transactional leadership exhibited in top-level management is positively related to internal integration within the manufacturing companies. Transformational leadership behavior exhibited in top-level management and advanced manufacturing technology implemented in the shop floor of these companies are positively related to the integration of external supply chain partners. In addition, we also found that in those instances where small manufacturing companies place a high emphasis on the implementation of advanced manufacturing technology, they are guided by transformational leaders who strongly integrate their companies with customers.
Keywords: Advanced manufacturing technology; Customer integration; Internal integration; Small manufacturing industries; Strategic leadership; Supplier integration; dept.mgt; peer-reviewed

Integration of Social Capital and Organizational Learning Theories to Improve Operational Performance - Birasnav, M.; Chaudhary, Richa; Scillitoe, Joanne (Global Journal of Flexible Systems Management, 2019)
This study focuses on integrating the premises of social capital theory and the theory of organizational learning to improve the operational performance of firms nurturing the buyer–supplier relationship. Social capital theory highlights the importance of developing social relationships between firms to create valuable resources and collectively access critical resources. Organizational learning theory highlights that the learning capacity of an organization strongly depends on top-level leaders’ behaviors, organizational structure, culture, and flexibility, and uncertainties in the environment in which the organization functions. Though many studies have focused on the impact of social capital on performance improvements in the buyer–supplier relationship, the interlinkages between social capital and organizational learning have not been given much attention. Based upon these theories, a system-focused perspective, which showcases the antecedents and outcome of the relationship between collaborative communication and learning, has been proposed in this study. A literature review has been carried out to support the linkages in the proposed conceptual model. Findings suggest that transformational buyers support creating cognitive capital with suppliers. This cognitive capital influences the structural capital, which supports improving the understanding of each party’s processes in the buyer–supplier relationship when parties have high long-term orientation. Improved learning capability reshapes organizations into flexible systems capable of responding quickly to customer requirements, and consequently, they realize a higher performance level.
Keywords: Collaborative communication; Information technology competency; Long-term orientation; Organizational learning; Supplier knowledge; Transformational leadership; dept.mgt

Integrating Theories of Strategic Leadership, Social Exchange, and Structural Capital in the Context of Buyer–Supplier Relationship: An Empirical Study - Birasnav, M.; Mittal, Rakesh; Dalpati, Avadhesh (Global Journal of Flexible Systems Management, 2019)
This study is aimed at improving the purchasing cycle time in a buyer–supplier relationship by integrating the facets of strategic leadership, social exchange, and social capital theories. We developed and tested a conceptual model that postulated relationships among strategic leadership behavior, relational trust and commitment, structural capital, and purchasing cycle time. Data were collected from purchase managers and their employees working in 105 manufacturing companies and analyzed using structural equation modeling technique. Our findings indicated that strategic leadership behaviors are positively related to trust in the buyer–supplier relationship. In addition, trust enhances relational commitment between buyer and supplier, which in turn positively relates to information sharing and supplier development. Further, increased information sharing in the relationship results in reduced purchasing cycle time. Implications for both theory and practice are discussed in depth, and directions for future research are suggested.
Keywords: Cycle time; Information sharing; Relational commitment; Relational trust-Strategic leadership; Supplier development; dept.mgt; peer-reviewed

Money and Morality: Leadership in the National Football League - Stewart, Carol; Joyner-McGraw, Laquita (Competition Forum, 2019)
Keywords: dept.mgt; peer-reviewed

Employee Assistance Programs: Balancing Increased Productivity and Engagement Among Employees with Equal Employment and Legal Complience - Smith, Robert A.; Badr, Kauther S.; Wall, Alison E. (Competition Forum, 2019)
Managing the impact of employees' personal and work-related difficulties on workplace productivity is becoming increasingly salient for organizations. Employee Assistance Programs (EAPs) are one approach to help improve the quality of life for employees and maximize their productivity. While EAPs have many benefits, potential negative ramifications and legal considerations must also be considered. This article highlights some important cases and the best practices for organizations to utilize in creating clear organizational policies that align with equal employment opportunity and privacy laws in collaboration with legal and human resources professionals and employee assistance providers to reduce or eliminate potential liability.
Num Pages: 232-239 Place: Indiana, United States
Keywords: Absenteeism; Affirmative action; Business And Economics; Complaints; Confidentiality; Costs; Employees; Employers; Employment discrimination; Human resource management; Labor law; Performance evaluation; Productivity; Sexual harassment; dept.mgt; peer-reviewed; ⛔ No DOI found

Participant carelessness: Is it a substantial problem with survey data? - Marasi, S.; Wall, A.; Brewer, K. (Electronic Journal of Business Research Methods, 2019)
For decades, participant carelessness has been considered a problem in collecting data using surveys. Although participant carelessness cannot be disputed to exist, the impact it has on data quality or the level of influence or bias it produces in results is questionable. The main purpose of this paper is to determine whether participant carelessness is a substantial problem that significantly influences or biases the results of statistical analyses. This is accomplished by analyzing established management relationships through a comparison of the full, careful, and careless samples to determine the impact participant carelessness has on data results regarding correlations, t-tests, and simple linear regressions. Four detection approaches were used to identify careless participants individually, in pairs, and in three method combinations. The second purpose of this paper is to use the resampled individual reliability (RIR) approach to detect careless participants and compare it to the individual reliability approach to determine whether the two approaches are fundamentally similar. Data were collected using Mechanical Turk (N = 678). Based on the findings, participant carelessness does not appear to be a substantial problem or demonstrate levels of bias in the results in this study. There are two significant differences between the full and careful samples with the t-tests and the regression comparisons of fit statistics demonstrate the careful samples to have a weak improvement over the full sample however, none indicate bias. The findings also suggest that the individual reliability and the RIR approaches are not entirely fundamentally similar. © ACPIL.
Keywords: Careless responding; Insufficient effort responding; Participant carelessness; Random responding; dept.mgt; peer-reviewed; ⛔ No DOI found

Chatbots for Multilingual Conversations - Vanjani, Mahesh; Aiken, Milam; Park, Mina (Journal of Management Science and Business Intelligence, 2019)
Chatbots emulate human dialogue to provide a more intuitive user interface to applications or simply provide entertainment. Chatbots rely on technology to function and new and emerging technologies such as NLP (Natural Language Processing) and AI (Artificial Intelligence) can be used to increase the ability of chatbots to emulate a more natural and free flowing conversation. As more and more mobile device users transition to increased use of texts and messaging chatbots can be used to provide consumers with multilingual support and services. While some chatbots have been developed in other languages, currently most converse only in English, and only a few can communicate in multiple languages. If configured correctly multilingual chatbots have the potential of providing a digital communication option that transcends language barriers. For our research we focused on the use of a chatbot that links the English-speaking Tutor Mike system with Google Translate, thus providing conversational capability in 103 languages, which is more than any other artificial multilingual agent is currently capable of. Two humans communicated with the system using German, Spanish, and Korean, and a group of undergraduate students reviewed the English translations of the chatbot’s replies. Results show that the responses from German and Spanish were cogent and natural, but those from Korean were less understandable. As a caveat, Asian languages lack much of the linguistic nuances of European languages. For example, there may be no plural form or gender in the Asian language. Unlike German where nouns and adjectives constantly change endings depending on what they are doing in a sentence and, unlike Spanish, which have numerous verb conjugations, Asian languages require no such changes. This might impact the translation ability and quality of a multilingual chatbot. Additional research and enhancements can improve chatbots used for European to Asian language translations and vice-versa. Regardless, our research shows promising results in the future use of multilingual chatbots to allow communication across the globe with business potential in the use of such chatbots to provide customer service and online live interaction with customers across the world.
Keywords: Chatbot; Multilingual; Communication; Machine Translation; dept.bis; dept.mgt; peer-reviewed

Should employees be “dooced” for a social media post? The role of social media marketing governance - Parker, Janna M.; Marasi, Shelly; James, Kevin W.; Wall, Alison (Journal of Business Research, 2019)
Instances of employees being `dooced' because of a social media post are becoming commonplace. Three research questions are presented to better understand workplace firings due to social media posts using justice theory and social convergence to fit within the nomological net. The first question examines employees' awareness of their employer's social media policy. The second question examines the role of offensiveness in the perceived fairness of the termination. The third question asks whether work-related posts (social convergence) and the presence of a social media policy (social media governance) influence the perception of termination fairness. Two data collection efforts are presented to test the research questions. The research findings extend the social media marketing governance literature by incorporating role theory and script theory. Managerial implications include the importance of developing and communicating to employees the organization's social media policies.
11 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/064-072-744-556-090, pop00132 tex.type: [object Object]
Keywords: Justice theory; Role theory; Script theory; Social convergence; Social media marketing governance; Termination fairness; dept.mgt; peer-reviewed

Soft skill development in a total enterprise simulation - Frank, Ellen J (Business Education Innovation Journal, 2019)
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

Participant carelessness: Is it a substantial issue in survey research? - Marasi, S.; Wall, A.; Brewer, K. (Electronic Journal of Business Research Methods, 2019)
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

Automated translation preference with a bilingual chatbot - Park, Mina; Aiken, Milam (International Journal of Computers & Technology, 2019)
Free, online language translation services are being used by people around to the world to facilitate communication. However, it takes time and effort for a person to load the Web page in a browser, copy and paste text into the site, and translate words. The process quickly becomes tiresome. Instead, some computer programs are providing automated translation. However, no studies have been conducted to determine the efficiency or effectiveness of such an approach. In this study, we compare how students used an English-based chatbot with and without German automatic translation. Results show that students took nearly 1.5 times longer than their stated upper time limit to manually translate. In contrast, the automated translation was at least 30 times faster. In addition, the students were significantly more satisfied with the automated than the manual system.
2 citations (Crossref) [2023-10-31] Citation Key Alias: pop00215 tex.type: [object Object]
Keywords: Chatbots; Google Translate; Tutor Mike; artificial conversation; dept.bis; dept.mgt; machine translation; peer-reviewed